Job belonging among healthcare workers in radiology departments in Saudi Arabia - Rowa Aljondi; Salem Saeed Alghamdi; Samaher Alyanbawi; Abdulrzzag Alghamdi; Bander Alshomrani; Zuhier Awan; Khalid Alsafi; Abdulrahman Tajaldeen; Essam Mattar; Abdullah R. Khazindar; Abdelmoneim Sulieman (Journal of Radiation Research and Applied Sciences, 2022)
Background: job satisfaction among healthcare workers plays a crucial role in improving radiology service, including diagnosis of imaging, disease monitoring, therapy guidance, and treatment plans. Purpose: This study aimed to examine job belonging and its associated factors among healthcare workers in radiology departments in Saudi Arabia. Materials and methods: In April 2021, an online cross-sectional survey was administered to all healthcare workers among various radiology departments in different regions of Saudi Arabia. The questionnaire contained sociodemographic characteristics, occupational characteristics, and a 25-item survey that measured participant job belonging in three dimensions: professional belonging, social belonging, and administrative belonging. Data were analyzed using SPSS software version 26. Results: and Discussion: A total of 212 radiology department healthcare workers participated in the survey. Age distribution was dominated by respondents between 26 and 35 years of age. Study participants reported overall high scores of professional belonging at 2.47/3, social belonging at 2.57/3, and an average score of administrative belonging at 1.97/3. Sociodemographic factors affected job belonging among healthcare workers in radiology departments, and these factors consisted of age, gender, and marital status. Conclusions: Participants with more than five years of experience in radiology had higher professional belonging, while higher education influenced the level of professional and administrative belonging. Salary, promotions, and workload were elements influencing overall professional and administrative job belonging scores. Our findings revealed a high level of professional and social job belonging among healthcare workers in radiology departments in Saudi Arabia. This study contributes to current knowledge related to job satisfaction of healthcare workers, and its findings suggest that job belonging in the work setting is influenced by certain sociodemographic and occupational factors.